Meteorites in the orchard: on the structuring potential of functional integration (Orfeu, 2020)
From Monteverdi to Mahler, R. Strauss and young Schoenberg, tonality has constantly challenged its very morphological bases and, moreover, it has proved to be rich in terms of forms and formal procedures. The main aim of this paper is to demonstrate the structuring potential of a compositional procedure I call functional integration, which consists in contextually imbuing functionality into chords, melodic excerpts etc. conceived by means other than functional tonality. For this purpose, I present the minimal morphological criteria for the structuring properties of tonality to work (e. g., the functional relations between sections of a work or the relations of reciprocity between local and larger scale levels of harmonic organization); and I report the compositional process of a clarinet piece, in which a process of functional integration is performed. In particular, I conclude that such a procedure has, above all, favored a constant attitude of discovery towards both tonality and the unique resulting form.
Keywords: Music composition; functional tonality; musical form; functional integration